2016
DOI: 10.1007/s13437-016-0107-7
|View full text |Cite
|
Sign up to set email alerts
|

A proposed quantitative methodology for the evaluation of the effectiveness of Human Element, Leadership and Management (HELM) training in the UK

Abstract: In 2006, a review of maritime accidents found that non-technical skills (NTSs) are the single largest contributing factor towards such incidents. NTSs are composed of both interpersonal and cognitive elements. These include things such as situational awareness, teamwork, decision making, leadership, management and communication skills. In a crisis situation, good NTSs allow a deck officer to quickly recognise that a problem exists and then harness the resources that are at their disposal to safely and efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…In contrast to the assessment systems and rating scales for BRM training that have been published so far (e.g., Saeed et al, 2017…”
Section: Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the assessment systems and rating scales for BRM training that have been published so far (e.g., Saeed et al, 2017…”
Section: Behaviourmentioning
confidence: 99%
“…Although the STCW do not prescribe a certain training method, the common line of argument is that trainees must experience and perform teamwork and leadership behaviours in order to develop the required skills. Accordingly, studies on the effectiveness of classroom-based resource management training so far show hardly any transfer to applications in the simulator (Saeed et al, 2017) or in the real world (Röttger et al, 2016). While the use of simulators for resource management training seems to be more promising, designing and implementing such training may be difficult for two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…In the maritime domain, however, it has been claimed that NTS knowledge currently in use in BRM training primarily stems from other domains (such as aviation) and even that indications of poor effects of BRM training are partly caused by the lack of adaptation of the syllabus to the maritime domain (O'Connor 2011). Some effort has been made to develop preliminary NTS taxonomies and behavioral markers (Conceição et al 2017;O'Connor and Long 2011;Saeed et al 2017). However, reviews in the domain have indicated that there is still a need for further exploration of NTS in this setting (Fjeld et al 2018;Hetherington et al 2006;Wahl and Kongsvik 2018).…”
Section: Brm Training and The Importance Of Bridge Officers' Understamentioning
confidence: 99%
“…A number of authors, such as Saeed, Wall, Roberts, Riahi, & Bury (2017) and others consider the issue of assessing the effectiveness of the personnel management system taking into account the specifics of the activity of the object of research, its industry sector.…”
Section: Approaches To Efficiency Assessment Of Personnel Service Permentioning
confidence: 99%